Efektivitas Konseling Behavioral Teknik Reinforcement untuk Meningkatkan Kepercayaan Diri pada Siswa Tunanetra : The Effectiveness of Behavioral Counseling Reinforcement Techniques to Increase Self-Confidence in Blind Students - Umam, Muhamad Safiul; Lestari, Prima Harsi Kantun (Universitas Pendidikan Ganesha, 2025)
Self-confidence is a fundamental element in supporting the growth and development of blind students. Without self-confidence, the learning process of blind students can be disrupted, social relationships are limited, and the development of independence is hampered. To create an inclusive and empowering learning environment, efforts to increase the self-confidence of blind students must be a priority. One of the counseling approaches that can be used to increase self-confidence is Behavioral counseling with reinforcement techniques. The purpose of this study was to test the effectiveness of Behavioral counseling with reinforcement techniques to increase self-confidence in blind students. The design of this study was a one group pretest-posttest design with a population of seven blind students at SLB Negeri 1 Bangli, the technique used in sampling was purposive sampling. Due to the limited sample, the statistical test used was the Wilcoxon test with α = 5%. H0 is rejected if the statistical test <Wilcoxon Table, H0 is accepted if the statistical test ≥ Wilcoxon Table. Based on the test analysis, the value of 0 <2 was obtained, so it can be concluded that the Behavioral counseling approach with reinforcement techniques is effective in increasing the self-confidence of blind students.